Bom dia para renascer: as crônicas de Otto Lara Resende para a Folha de S. Paulo - Chagas, Carolina de Bartolo (2006)
This study analyzes the journalistic work of Otto Lara Resende (1922 1992) based on columns he published in the newspaper Folha de S.Paulo from 1991 to 1992. It describes the support in which the columns exist the newspaper and discusses the importance of this writing genre for the periodicals. It also provides an overview of journalistic columns in Brazil, describing influences evinced by the columns over the decades. Some of the 523 columns that Otto Lara Resende wrote for the Folha de S.Paulo are selected to demonstrate features of this columnist s writing, such as irony, criticism and the use of day-to-day life. The texts by Otto concerning the Collor Era, a period of recent Brazilian history marked by intense activity by the press, are given a special focus. Having arisen in France at the end of the 19th century, the practice of writing and publishing columns soon arrived in Brazil, and with the overall development of the press in the 20th century the column s role was consolidated and took on peculiarities that became established as distinctively Brazilian characteristics. The newspaper column has been a starting point for various writers who became known for their column writing, including Rubem Braga, Paulo Mendes Campos, Antônio Maria and Otto Lara Resende himself. He was a journalist in the widest sense of the term having worked in all sectors of newspaper production: reporting, editing, report planning, editorials and authored several books including O Braço Direito and Boca do Inferno. His last columns display striking characteristics, as described in this study. His columns for the Folha are a good example of the blending of different fields journalism and literature which is typical of Brazilian periodicals, giving rise to reflections on current journalistic practice